2020
DOI: 10.5194/tc-2019-294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New gravity-derived bathymetry for the Thwaites, Crosson and Dotson ice shelves revealing two ice shelf populations

Abstract: Abstract. Ice shelves play a critical role in the long-term stability of ice sheets through their buttressing effect. The underlying bathymetry and cavity thickness are key inputs for modelling future ice sheet evolution. However, direct observation of sub-ice shelf bathymetry is time consuming, logistically risky, and in some areas simply not possible. Here we use airborne gravity anomaly data to provide new estimates of sub-ice shelf bathymetry outboard of the rapidly changing West Antarctic Thwaites Glacier… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…Troughs and channels in the adjacent eastern part of Pine Island Bay have been described comprehensively by Nitsche et al (2013) and Kirkham et al (2019). The larger troughs in our study area, which have also been identified on gravity-derived regional bathymetry maps (Millan et al, 2017;Jordan et al, 2020. ), are considered important as potential pathways for the transport of CDW towards the grounding zone of TG and warrant full description here.…”
Section: Trough and Channel Metricssupporting
confidence: 67%
See 4 more Smart Citations
“…Troughs and channels in the adjacent eastern part of Pine Island Bay have been described comprehensively by Nitsche et al (2013) and Kirkham et al (2019). The larger troughs in our study area, which have also been identified on gravity-derived regional bathymetry maps (Millan et al, 2017;Jordan et al, 2020. ), are considered important as potential pathways for the transport of CDW towards the grounding zone of TG and warrant full description here.…”
Section: Trough and Channel Metricssupporting
confidence: 67%
“…During ITGC cruise NBP19-02, the marine areas in front of TG were unusually clear of sea-ice and icebergs providing a unique opportunity for bathymetric data acquisition at the margin of Thwaites Ice Shelf (Larter et al, 2020). MBES data was acquired using a hull-mounted 1° x 1° Kongsberg EM122 echo sounder with 288 across-track beams and an operational frequency in the range 11.25-12.75 kHz.…”
Section: Multibeam Echosounder Datasets (Mbes)mentioning
confidence: 99%
See 3 more Smart Citations